Time Trade-Off Derived EQ-5D Weights for Australia - Viney, R.; Norman, Richard; King, M.; Cronin, P.; Street, D.; Knox, S.; Ratcliffe, J. (Wiley-Blackwell Publishing, Inc., 2011)
Background: Cost-utility analyses (CUAs) are increasingly common in Australia. The EuroQol five-dimensional (EQ-5D) questionnaire is one of the most widely used generic preference-based instruments for measuring health-related quality of life for the estimation of quality adjusted life years within a CUA. There is evidence that valuations of health states vary across countries, but Australian weights have not previously been developed.Methods: Conventionally, weights are derived by applying the time trade-off elicitation method to a subset of the EQ-5D health states. Using a larger set of directly valued health states than in previous studies, time trade-off valuations were collected from a representative sample of the Australian general population (n = 417). A range of models were estimated and compared as a basis for generating an Australian algorithm.Results: The Australia specific EQ-5D values generated were similar to those previously produced for a range of other countries, but the number of directly valued states allowed inclusion of more interaction effects, which increased the divergence between Australia’s algorithm and other algorithms in the literature.Conclusion: This new algorithm will enable the Australian community values to be reflected in future economic evaluations.